Mental Health Journal and Mood Tracker System - Alias, Nurjeha; Ibrahim, Noraini (Applied Information Technology And Computer Science, 2025)
Mental health has become increasingly important for individuals to manage daily stress, maintain emotional stability, and contribute positively to society. Addressing mental health requires constant monitoring and care, as conditions can fluctuate over time. Therefore, integrating technology into mental health care has become crucial to provide support and improve long-term outcomes for individuals affected. The Mental Health Journal and Mood Tracker System has been developed to enhance communication and data sharing between mental health professionals and their patients. The prototyping methodology has been used to develop this system, with tools such as Visual Studio Code as the source-code editor, along with MySQL, XAMPP, and PhpMyAdmin for database storage. This system includes several key modules: the login and register, manage profile, schedule appointment, assess mental health, track journal and mood, manage medication, and generate report. The system is expected to make a significant contribution to the mental health community, as it enhances communication between professionals and patients by allowing patients to update their condition regularly. Additionally, it reduces reliance on patients’ ability to recall and summarize their history before appointments.